Acute and subacute toxicity study of ethanolic extract of Calotropis procera (Aiton) Dryand flower in Swiss albino mice - Ashutosh Kumar; Brijesh Kumar; Rajesh Kumar; Ajay Kumar; Manish Singh; Vinod Tiwari; Anshuman Trigunayat; Paramita Paul; Pratistha Singh (Elsevier, 2022)
Background: Calotropis procera is a large shrub which consists many medicinal properties, used in treatment of snake bite, sinus fistula, rheumatism, mumps, burn injuries, inflammation and jaundice traditionally. All the parts of Calotropis procera were utilized in the treatment of diseases out of which leaves and roots were investigated for its toxicity profile that showed dose dependent toxicity. Toxicity profile of flowers of Calotropis procera was not investigated in the previous studies. The aim of this study was to explore the acute and subacute toxicity of ethanolic extract of Calotropis procera flowers for the safe use of traditional medicine. Method: In acute toxicity, a total of 20 female mice (Swiss albino), weighing between 23 and 32 g were randomly divided into four experimental groups: control, 300, 1000, and 2000 mg/kg groups with 5 mice each, and each received a single dose of extract at 300, 1000, or 2000 mg/kg, respectively. Animals were monitored for 14 days. In the subacute study, a total of 40 mice (23-32 g) were divided into 4 groups, each containing males and females. Group 1 (control group) received vehicle and groups 2, 3, and 4 received extract at doses of 300 mg/Kg, 1000 mg/Kg, 2000 mg/Kg of b.w., respectively, for 28 consecutive days. The study was conducted in compliance with the OECD guidelines 407 and 423. Results: Acute toxicity study showed no mortality at the dose of 2000 mg/Kg. In subacute toxicity study, statistical analysis of hematological and biochemical parameters showed no significant differences compared to control group except marked increase in segmented neutrophils. Histopathological studies revealed no significant structural differences among the treated groups and in comparison to control group. Conclusions: It was concluded that oral administration of doses of ethanolic extract of Calotropis procera flower, administered acutely, did not cause any mortality or notable changes at the dose of 2000 mg/Kg. Therefore, the approximate lethal dose (ALD) of in mice was higher than 2,000 mg/kg. In a 28-day subacute toxicity model, the extract did not cause any mortality, and no treatment-related changes were observed in body weight, organ weight, hematological and biochemical blood analysis, or histopathologic examinations at the extract dose of 2000 mg/Kg. These findings indicate that the no-observed-adverse-effect-level (NOAEL) of Calotropis procera flower ethanolic extract was greater than 2000 mg/kg/day.